Strategic Intellectual Property Management and Intrapreneurship: Leveraging Talent Development for Competitive Advantage in the Indonesian Film Industry - Chakalica Widyadipraja; Amie Kusumawardhani (Universitas KH. Abdul Chalim Mojokerto, 2024)
This study analyzes the strategies of intellectual property (IP) management, talent development, and the role of intrapreneurship performance in the film industry, as well as the implications of the Resource-Based View (RBV) Theory on the business potential of companies. A comprehensive approach to IP management includes identification, valuation, and legal protection, recognizing creativity as a primary asset. This strategy maximizes the economic value and legal protection of each film production. Additionally, talent development and regeneration in the film industry are achieved through collaborations with educational institutions and internship programs, creating a work environment that supports creativity and innovation. Intrapreneurship performance is a key factor in achieving a competitive advantage. A strong culture of innovation and entrepreneurship enables companies to support employees' creative ideas through internal programs and competitions, providing a competitive edge that is difficult for competitors to replicate. From an RBV perspective, film companies have significant business potential by leveraging unique resources and capabilities, such as a culture of innovation and talent development programs. Theoretical implications suggest that integrating IP management, entrepreneurship performance, and RBV can build a sustainable business strategy. Companies are advised to focus on IP protection, support intrapreneurship performance, and develop talent to maintain competitive advantage, using RBV for long-term growth strategies through sustainable innovation and effective resource management.